VD_FINDINFO Décision / 2014 / 97 vom 12. November 2013 - VD Tribunal cantonal (2013)
CLASSEMENT DE LA PROCÉDURE, PLAINTE PÉNALE, RETRAITVOIE DE DROIT | 33 al. 1 CP, 33 al. 2 CP, 33 CP, 319 al. 1 CPP (CH), 319 CPP (CH)